Corporate Governance Bank Syariah Sebuah Tantangan Profesionalitas - Fahrur Ulum (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2010)
For the future expansion, shariah banks need the capacity of its human resources in understanding the banking system. Islamic banking must be committed to improve its performanceÂ  and to fulfil the aspiration of its stakeholders by applying corporate governance effectively. In so doing, it will create fairness, transparency and accountability. There are certain aspects which have to be clearly analyzed and prioritized by the players of islamic banking in implementing corporated governance for islamic banking such as its basic concept, contracts clarity, market discipline, moral dimension, socio-political environment, and legal aspect. Parties which directly related to the mechanism of corporate governance of islamic bank, that are board of directors, senior management and share holders and depositors are important in creating harmony of islamic banking expansion. In addition, supporting infrastructures have to be improved for corporate governance, such as internal control, risk management, transparency, accounting and funding disclosure, purification and shariah audit, regulation and prudent monitoring.